Bridged composite right/left handed unit cell with all-pass and triple band response (2012)
A modified design of the composite right/left handed (CRLH) unit cell showing all-pass and triple band response is proposed. By using an additional inductance which cross-couples the input and output ports of the conventional CRLH, a bridged CRLH unit cell (B-CRLH) is created. This allows additional right-handed (RH) wave propagation below the cutoff frequency of the conventional CRLH to dc, forming a new low-frequency-RH band with a non-linear dispersion relationship. Meantime, a mid-frequency-LH band and a high-frequency-RH band, which are inherited from the conventional CRLH, are still present, resulting in triple band configuration. The dispersion relation and Bloch impedance of the B-CRLH are investigated by standard periodic analysis. Balanced conditions to close transitions between the three bands, to realize all-pass behavior, are derived. Full wave structure simulations show good agreement with circuital simulations and measurement. Also, a triband open-stub consisting of two B-CRLH unit cells is demonstrated as an application example. © 2001-2012 IEEE.